High blood pressure in the pediatric age group - Andrade, H (2010)
The definition of hypertension (HT) in the pediatric age group is based on the normal distribution of blood pressure (BP) in healthy children. Normal BP is defined as being below the 90th percentile for gender, age and height, and hypertension as equal to or higher than the 95th percentile on at least three separate occasions. If the values are above the 90th percentile but below the 95th percentile, the child should be considered prehypertensive. Ambulatory BP monitoring is useful in the assessment of BP levels in the young. P values in children and adolescents have creased in the last decade, in parallel with increases in body mass index, and HT now has a prevalence of 2-5%. Obesity in childhood and adolescence is one of the main predictors of HT in adulthood, but it is also associated with other cardiovascular risk factors such as dyslipidemia, abnormal glucose metabolism, insulin resistance, inflammation and impaired vascular function. Left ventricular hypertrophy is the most prominent evidence of target organ damage caused by hypertension in children and adolescents. The goal for antihypertensive treatment is to reduce BP below the 95th percentile. Weight control, with regular physical activity and dietary changes, is the primary therapy for obesity-related hypertension. Weight loss decreases not only BP but also other cardiovascular risk factors. The indications for use of antihypertensive drugs are: symptomatic hypertension, secondary hypertension, established hypertensive target organ damage, stage 2 hypertension and failure of nonpharmacologic measures.